Designing and analysis of cross-shaped CRLH metamaterial for wide band negative index characteristics. (5th April 2019) - Singh, Harbinder; Sohi, Balwinder Singh; Gupta, Amit
Abstract: The compact sized cross-shaped metamaterial design is evaluated for single negative, double negative and double positive behavior for a wide range of frequencies to investigate the gap and gapless transition from backward to forward wave propagation near 17 GHz. The metamaterial designed in this study is analyzed for negative index characteristics of permittivity, permeability and refractive index over the broad range of frequencies. The dispersion diagram of the material is also investigated for left or right behavior of the material. The equivalent circuit diagrams along with circuit simulations of the parameters are also presented for detailed analysis and understanding. The designed metamaterial behaves like a double negative material for low frequencies below 17.23 GHz and double positive materials for high frequencies above 17.23 GHz. The design is simulated using CST Microwave studio and obtained results are authenticated using the wave-guide measurement technique.